An Assistance Processing Waste into Crafts to Increase the Creativity of TPQ Al Ikhlas Students at Tanjung Harapan Village - M. Aali Mustahfidzil M; Reno Tegar Pangestu; Malik Abdul Aziz; Refi Fadilah Oktavia; Habibi Fajri; Febri Ilham Nurcholis; Firman Adi Adam; Rafiqha Mufti; Rela Amalia; Nurliza Masroatul M; Siti Logaya; Yunita Sari; Isnaini Nur Azizah (Yayasan Payungi Smart Madani, 2024)
The service activity of UMALA Metro lecturers and students in Tanjung Harapan Village is